Khái quát về trí tuệ nhân tạo và hệ chuyên gia - Bao, Ho Tu (Journal of Computer Science and Cybernetics, 2018)
This paper presents essential concepts of Artificial Intelligence and Expert systems as well as its development history, actual situation and perspective.